A digital twin modeling approach for smart manufacturing combined with the UNISON framework. (July 2022) - Wang, Jinfeng; Zhang, Luyao; Lin, Kuo-Yi; Feng, Lijie; Zhang, Ke
Abstract: With the in-depth development of industry 4.0, digitalization and intellectualization have become a broad consensus, especially the digital twin. As a cutting-edge technology, the digital twin is revolutionizing the industry, but its potential is far from being tapped. Data and models, which have been proven in previous studies, are the core and foundation of the digital twin. However, most of the digital twin solutions have limitations in real settings. Previous models often neglected to provide a detailed description of the components or operational rules of the digital twin, which poses limits for practitioners. This is because there is not a completely unified understanding of the digital twin and not enough in-depth analysis of its components. This study aims to provide a methodology to construct a practical digital twin model. The method is based on the proposed five-dimensional digital twin model and the UNISON framework. To illustrate the structured procedures of this model, it was applied in an empirical study for the new energy power battery. The results have demonstrated the validity of the proposed framework. From the perspective of model construction, this study provides ideas and technical references for the application of the digital twin.